Factors associated with patterns of psychological distress, alcohol use and social network among Australian mineworkers - Carole James; Mijanur Rahman; Aaron Bezzina; Brian Kelly (Elsevier, 2020)
Abstract Objective: To investigate the convergence of individual findings relating to psychological distress, alcohol use and social network (SN) to identify their associated clusters within Australian mineworkers. Methods: This study used cross‐sectional survey data from 3,056 participants across 12 Australian mines. Latent class analysis used the scores of Kessler Psychological Distress Scale, Alcohol Use Disorders Identification Test (AUDIT) and Social Network Index. Results: Class 1 (moderate to very high psychological distress, low SN score and low to moderate AUDIT) included 39% (n=1,178) participants and class 2 (low to moderate psychological distress and AUDIT and very high SN) composed of 61% (n=1,873) participants. Class 1 was associated with younger age (OR=0.65, 95%CI=0.53‐0.81), being a current smoker (OR=1.45, 95%CI=1.18‐1.79), and reporting a history of anxiety (OR=3.00, 95%CI=2.23‐4.05) and/or depression (OR=2.18, 95%CI=1.65‐2.90). Conclusions: These findings highlight the challenges the mining sector faces regarding the welfare of its employees. Implications for public health: Modifiable work factors associated with lower social networks and higher psychological distress need addressing at an individual and industry level through targeted and specifically tailored multi‐component interventions.